Formation of carbon nanostructures in nuclear graphite under high-temperature in situ electron-irradiation. (March 2019) - Johns, Steve; Poulsen, Tyler; Kane, Joshua J.; Windes, William E.; Ubic, Rick; Karthik, Chinnathambi
Abstract: Defect evolution in nuclear graphite has been studied in real time using high-temperature in situ transmission electron microscopy. In situ electron-irradiation was conducted at 800 °C on a 200 kV transmission electron microscope with a dose rate, given in terms of displacements per atom per second, of approximately 1.46 × 10 −3 dpa/s. Defect domains consisting of ordered arrangements of pentagons, hexagons, and heptagons exist intrinsically in nuclear graphite and in addition are readily produced via electron-irradiation; however, at elevated temperatures these defect domains undergo atomic rearrangements resulting in the formation of carbon nanostructures via curling and closure of the basal planes. The formation of fullerenes and other structures due to thermal annealing or high-temperature electron-irradiation has been observed in disordered regions of the microstructure and interstitially between basal planes. These defect structures result in localized swelling and expansion of crystallites along the c axis; thus, it is proposed as one of the many atomic mechanisms involved in the dimensional change of nuclear graphite subjected to high-temperature irradiation. Graphical abstract: